Minority governments and party politics: The political and institutional background to the Danish Miracle - Christoffer Green-Pedersen (Max-Planck-Institut für Gesellschaftsforschung, 2001)
The performance of the Danish economy in the 1990s has been successful to the extent that scholars are talking about a Danish miracle. The importance of government policies to Denmark's economic success is taken as a point of departure in investigating why Danish governments have been able to govern the economy successfully in the 1990s. The paper argues that two factors have been important. First, the functioning of Danish parliamentarianism has been reshaped to strengthen the bargaining position of minority governments, which became the rule in Danish politics after the landslide election in 1973. Today, Danish minority governments can enter agreements with changing coalitions in the Danish parliament. The paper thus challenges the conventional wisdom about minority governments as weak in terms of governing capacity. Second, the changed socio-economic strategy of the Social Democrats after returning to power in 1993 has been important because it has created a political consensus around a number of controversial reforms. – – Der Erfolg der dänischen Wirtschaft in den 90er Jahren lässt Fachleute von einem dänischen Wunder sprechen. Die große Bedeutung der Regierungspolitik für den wirtschaftlichen Erfolg Dänemarks dient als Ausgangspunkt für eine Untersuchung der Bestimmungsfaktoren der erfolgreichen Wirtschaftspolitik dänischer Regierungen in den 90er Jahren. Der Autor des vorliegenden Papiers sieht hierfür zwei grundlegende Erklärungsfaktoren. Zum einen wurde mit der Neuordnung des dänischen Parlamentarismus die Verhandlungsposition von Minderheitsregierungen gestärkt, die nach dem erdrutschartigen Wahlergebnis von 1973 zur Regel geworden waren. Heute können Minderheitsregierungen im dänischen Parlament mit wechselnden Koalitionspartnern Vereinbarungen treffen. Der Autor stellt mithin die gängige Ansicht in Frage, dass Minderheitsregierungen nur über eine geringe politische Durchsetzungsfähigkeit verfügen. Zum anderen haben die Sozialdemokraten nach ihrer Rückkehr in die Regierung im Jahre 1993 ihre bisherigen sozial- und wirtschaftspolitischen Vorstellungen korrigiert und damit zur Bildung eines politischen Konsenses über eine Reihe bis dato kontroverser Reformen beigetragen.
Keywords: 300